2016
DOI: 10.1007/s11837-016-1816-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partition of Photo-Initiator Components and Addition of Iodonium Salt on the Photopolymerization of Phase-Separated Dental Adhesive

Abstract: The polymerization kinetics of physically separated hydrophobic- and hydrophilic-rich phases of a model dental adhesive have been investigated. The two phases were prepared from neat resin containing 2-hydroxyethyl methacrylate (HEMA) and bisphenol A glycerolate dimethacrylate (BisGMA) in the ratio of 45:55 (wt/wt). Neat resins containing various combinations of popular photo-initiating compounds, e.g., camphoquinone (CQ), ethyl 4-(dimethylamino)benzoate (EDMAB), 2-(dimethylamino)ethyl methacrylate (DMAEMA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…As mentioned earlier with the conventional photosensitizer camphorquinone (CQ), almost no polymerization of the hydrophilic-rich phase was observed, and in the presence of an iodonium salt it could reach 20% to 32% depending on the co-initiator (Abedin et al ., 2016). The proposed candidate molecules have a significantly higher DC which is an improvement over the camphorquinone for the hydrophilic-rich phase.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…As mentioned earlier with the conventional photosensitizer camphorquinone (CQ), almost no polymerization of the hydrophilic-rich phase was observed, and in the presence of an iodonium salt it could reach 20% to 32% depending on the co-initiator (Abedin et al ., 2016). The proposed candidate molecules have a significantly higher DC which is an improvement over the camphorquinone for the hydrophilic-rich phase.…”
Section: Resultsmentioning
confidence: 86%
“…In our previous studies, it was observed that DC of the hydrophilic-rich phase mimics was in the range of 63% to 97% given that the photo-initiator concentration was sufficient (Abedin et al ., 2014; Abedin et al ., 2015c). In another study, it was observed that the DC of the hydrophilic-rich phase for physically separated model dental adhesive system was approximately 20% to 32% in presence of a reaction accelerator, iodonium salt (Abedin et al ., 2016). The low DC for this case was most likely due to the lack of either or both photosensitizer/co-initiator or low efficiency of the co-initiator within the hydrophilic-rich phase (Abedin et al ., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average of the last 50 values of the time-based spectra is reported as the DC value. The maximum polymerization rate false(RPmax/false[Mfalse]false) was determined using the maximum slope of the linear region of the DC vs. time plots [34, 36]. …”
Section: Methodsmentioning
confidence: 99%